Segmentasi Nasabah Bank Syariah: Hubungan Antara Variabel Demografi dengan Variabel Manfaat Pada Bank Muamalat Surakarta - Agus Marimin (ITB AAS INDONESIA Surakarta, 2015)
The development of sharia banking industry in Indonesia is quite rapidly in the last one decade. The sharia banks in nowadays just use the differentiation strategy, which is free from riba to compete with conventional banks. The method which is used in this research is quantitative method. While the research data is found by giving questioner to 50 respondents, they are customer of Muamalat Bank branch Solo To be able to compete in inter-bank sharia, they need to have appropriate segmentation strategy. Benefit segmentation including in the unobservable product specific based which can not be observed is a potential segmentation method which can be used by sharia banks, beside demographic segmentation including in observable general based product. This research tries to do the benefit and demographic segmentation benefit for sharia bank customers, and the research also searches the relationship between demographic variables and the benefit variable. This study uses chi square test,and cluster analysis to find out the relationship between the two variables. Keyword : segmentation, demographic segmentation, benefit segmentation, sharia banking.